2020
DOI: 10.1111/cmi.13294
|View full text |Cite
|
Sign up to set email alerts
|

A conserved malaria parasite antigen Pb22 plays a critical role in male gametogenesis inPlasmodium berghei

Abstract: Gametogenesis, the formation of gametes from gametocytes, an essential step for malaria parasite transmission, is targeted by transmission‐blocking drugs and vaccines. We identified a conserved protein (PBANKA_0305900) in Plasmodium berghei, which encodes a protein of 22 kDa (thus named Pb22) and is expressed in both asexual stages and gametocytes. Its homologues are present in all Plasmodium species and its closely related, Hepatocystis, but not in other apicomplexans. Pb22 protein was localised in the cytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…Further analysis showed that the defects of the Pb22 knockout (KO)line were limited to the male gametes, and the female gametes in Pb22-KO line were fertile at the wild-type level, indicating that Pb22 was indeed a key protein in the development of male gametes. Of the Pb22-KO line male gametocytes, 30% failed to assemble axonemes, whereas ~ 48.9% formed flagella but failed to egress from the host erythrocytes ( Liu et al, 2021 ). In addition, antibodies against the highly conserved Plasmodium berghei pleckstrin homology gene PbPH that is localized on the surface of gametes, zygotes, and ookinetes significantly inhibited the exflagellation of male gametocytes and the formation of ookinetes in a concentration-dependent manner ( Kou et al, 2016 ).…”
Section: Transmission-blocking For Plasmodium Sexu...mentioning
confidence: 99%
“…Further analysis showed that the defects of the Pb22 knockout (KO)line were limited to the male gametes, and the female gametes in Pb22-KO line were fertile at the wild-type level, indicating that Pb22 was indeed a key protein in the development of male gametes. Of the Pb22-KO line male gametocytes, 30% failed to assemble axonemes, whereas ~ 48.9% formed flagella but failed to egress from the host erythrocytes ( Liu et al, 2021 ). In addition, antibodies against the highly conserved Plasmodium berghei pleckstrin homology gene PbPH that is localized on the surface of gametes, zygotes, and ookinetes significantly inhibited the exflagellation of male gametocytes and the formation of ookinetes in a concentration-dependent manner ( Kou et al, 2016 ).…”
Section: Transmission-blocking For Plasmodium Sexu...mentioning
confidence: 99%
“…Also, exhaustion of the Metallo-dependent protein phosphatase PPM1 in P. berghei causes impaired exflagellation ( Guttery et al., 2014 ), while reducing the Ca 2+ -dependent phosphatase calcineurin affects male gametogenesis and subsequent fertilization in the rodent malaria parasite ( Philip and Waters, 2015 ). Recently, another protein in P. berghei , Pb 22 is characterized to have an essential function in male gametogenesis by producing defective male gametes, which further affects egress, fertilization and ookinete formation ( Liu et al., 2021 ). Though Pb 22 is expressed in the membrane of both male and female gametes, it has no significant role in female gametogenesis, as proved by the cross-fertilization of male and female gametes of the Pb 22KO line with wild strains ( Liu et al., 2021 ).…”
Section: The Criticality Of Gametogenesis and Its Biologymentioning
confidence: 99%
“…Similarly, a gamete/ookinete surface protein of P. berghei, Pb22, was identified and recombinant Pb22 was expressed in E. coli. The Pb22-immunised mice had a significant TRA (93.5-99.6%) (Liu et al, 2021). 1) are categorized as pre-fertilization antigens (mainly expressed in the sexual stages of parasites before fertilization), and post-fertilization antigens (mainly expressed in the sexual stages of parasites after fertilization).…”
Section: Rodent Malaria Models For Novel Tbv Candidate Discoverymentioning
confidence: 99%
“…Similarly, a gamete/ookinete surface protein of P. berghei , Pb22, was identified and recombinant Pb22 was expressed in E. coli . The Pb22-immunised mice had a significant TRA (93.5-99.6%) ( Liu et al, 2021 ).…”
Section: Rodent Malaria Models For Novel Tbv Candidate Discoverymentioning
confidence: 99%